Kajian Geoteknik Untuk Desain Pit Tambang Batugamping Di Daerah Karang Dawa, Kecamatan Margasari, Kabupaten Tegal, Jawa Tengah - Mersi Abadi; Arifudin Idrus; I Gede Budi Irawan Budi Irawan (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2018)
Location of research situated in the village Karangdawa, district Margasari, Tegal Regency, Central Java. The location of the research is the exploration Licences PT. Indocement Tunggal Prakarsa Tbk., with commodities limestone. This research is aimed at mengetahuikualitas, batugampingserta reserves and resources geotechnical model based on the geological model. Geotechnical models also determined based on the model of rockmass used slope stability analysis as a model to design the mine pit. The methods used in this research include field work in the form of observation of outcrops of rocks and develop the sample, as well as laboratory analysis in the form of analysis of petrographic analysis and XRF using the sample surface, analysis of physical and mechanical properties of the rock mass classification, as well as rocks based on Geological Strenght Index (GSI) uses a secondary data in the form of core data drilling. Analysis of the stability of slopes in this study using the method of limit equilibrium (limit equilibrium method). Interpretation and correlation of data indicating that the drilling core location stratigraphic research is composed by three units of rock: limestone, batulempung, as well as sandstones. XRF analysis results and modeling geology suggests the quality of limestone meet cement raw material standards as to the amount of 13,180,000 tons of limestone resources. The geometry of the slope resulting from the analysis of the stability of slopes of which are: single slope height of 10 meters, the angle of slope of a single 80-degree slope, the slope of the overall 48 degrees, 50 degrees, 60 degrees, 54 degrees, the wide level of 8.31 meters. Limestone reserves estimation is determined only on the basis of consideration of the mine pit design and ultimate pit limit which is limited by the territory of IUP. Backup tertambang (mineable reserve) limestone amounted to 7,477,000 tonnes.